Producing and Manipulating Information: Private Information Providers versus Public Information Providers - Robert A.J. Dur; Otto H. Swank (Tinbergen Institute, 2001)
This paper studies the selection of information collecting agents by policy makers in the light of two agency problems. First, it is often hard to ascertain how much effort agents have put in acquiring information. Second, when agents have an interest in the policy outcome, they may manipulate information. We show that unbiased advisers put highest effort in collecting information. Eliminating manipulation of information, however, requires that the preferences of the policy maker and the adviser be aligned. Therefore, policy makers appoint advisers with preferences that are less extreme than their own.
Keywords: 330; Politikberatung; Manipulation; Theorie; Politische Entscheidung